2009
DOI: 10.1039/b815718a
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of single hematopoietic stem cell fates in artificial niches

Abstract: Hematopoietic stem cells (HSCs) are capable of extensive self-renewal in vivo and are successfully employed clinically to treat hematopoietic malignancies, yet are in limited supply as in culture this self-renewal capacity is lost. Using an approach at the interface of stem cell biology and bioengineering, here we describe a novel platform of hydrogel microwell arrays for assessing the effects of either secreted or tethered proteins characteristic of the in vivo microenvironment, or niche, on HSC fate in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
160
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(165 citation statements)
references
References 52 publications
(100 reference statements)
4
160
1
Order By: Relevance
“…However, importance of N-cadherin for HSC-niche interactions was later questioned (Kiel et al, 2007), thus rising substantial controversy. In an elegant in vitro study Lutolf et al (2009) have shown that N-cadherin, as well as Wnt3a, are the only proteins among those tested that were capable of supporting self-renewal divisions of HSCs in vitro. N-cadherin expression was also shown to be important for maintenance of long-term repopulating cells in culture (Hosokawa et al, 2010).…”
Section: Expansion and Selection Of Genetically Modified Hscs Ex Vivomentioning
confidence: 99%
“…However, importance of N-cadherin for HSC-niche interactions was later questioned (Kiel et al, 2007), thus rising substantial controversy. In an elegant in vitro study Lutolf et al (2009) have shown that N-cadherin, as well as Wnt3a, are the only proteins among those tested that were capable of supporting self-renewal divisions of HSCs in vitro. N-cadherin expression was also shown to be important for maintenance of long-term repopulating cells in culture (Hosokawa et al, 2010).…”
Section: Expansion and Selection Of Genetically Modified Hscs Ex Vivomentioning
confidence: 99%
“…72 HSC behavior was analyzed in vitro by live-cell microscopy in combination with in vivo transplantation assays. To 'deconstruct' and mimic HSC niches, PEG hydrogel microwells were selectively functionalized at the bottom with regulatory proteins using a combination of soft lithography and microcontact printing (Fig.…”
Section: Analyses Of the Dynamics Of Single Adult Stem Cell Fate In Mmentioning
confidence: 99%
“…6). 72 Using automated time-lapse microscopy, the kinetic proliferation profiles of single cells were quantified, for example, as the distribution of numbers of HSC progeny generated per microwell as a function of time (Fig. 6).…”
Section: Analyses Of the Dynamics Of Single Adult Stem Cell Fate In Mmentioning
confidence: 99%
“…The application of such artificial ECMs (aECMs), and in particular their fabrication with well-defined physicochemical bulk properties, has also enabled researchers to gain insights into the biology of crosstalk between cells and microenvironmental components (for example, refs [3][4][5]. However, the control over bulk gel properties is often not sufficient to elicit a desired morphogenetic response and to ultimately form a functional tissue de novo.…”
mentioning
confidence: 99%
“…3f). ProteinA contains five high-affinity binding sites (K a = 10 8 per mole) for the Fc-region of human, mouse and rabbit immunoglobulins, and thus allows for easy, site-selective immobilization of Fc-tagged proteins 4 , many of which are commercially available. To this end, we modified ProteinA with caged Q-peptides and enzymatically patterned it within hydrogels.…”
mentioning
confidence: 99%